Doing Disability Research in the Majority World: an Alternative Framework and the Quest for Decolonising Methods - Grech, Shaun; Goodley, Dan (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change, 2011)
Research on disability in the so-called majority world remains scarce, and that which exists, continues to be dominated by Western epistemologies and methods, transferred indiscriminately from the global North to the global South. Unfortunately, the cultural and contextual relevance of these approaches remain largely unquestioned, a dynamic premised on the assumption that theories and methods bred in Western spaces are not only superior but applicable to all and sundry. This is what we term the neocolonisation of research. In order to challenge this, our paper takes up Tuhiwai Smith’s (1999) call for decolonizing research, by exploring the potential for a conceptual framework blending elements from poststructuralism, post and neo-colonialism, and Hardt and Negri’s (2000) work on Empire to engage more meaningfully with the study of disability across global contexts.